CCMAlnc Promotes the Malignance of Colorectal Cancer by Modulating the Interaction Between miR-5001-5p and Its Target mRNA - Yan, Yuqing; Xuan, Baoqin; Gao, Ziyun; Shen, Chaoqin; Cao, Yingying; Hong, Jie; Chen, Haoyan; Cui, Zhe; Ye, Guangyao; Fang, Jing-Yuan; Wang, Zhenhua (Frontiers in Cell and Developmental Biology, 2020)
Objective: Colorectal cancer (CRC) is highly malignant and cancer metastasis remains the predominant cause of CRC death. The potential molecular mechanism of long noncoding RNA (lncRNAs) in CRC malignance is still poorly elucidated. Methods: CCMAlnc expression was analyzed by using the Sequence ReadArchive (SRA) database. Target gene expression was examined by real-time PCR and Western blotting. The biological function of CCMAlnc and miR-5001-5p was detected by cell invasion, CCK8 proliferation and colony formation assays in loss of function and gain of function experiments in vitro. A luciferase assay was performed to validate the target site of miR-5001-5p on the 3’-UTR of HES6 mRNA. Results: CCMAlnc was identified as a novel functional lncRNA in CRC. Elevated CCMAlnc was detected in CRC cells as well as in clinical CRC tissue samples, and the expression of this lncRNA positively correlated with the poor prognosis of CRC patients. Functional validation assays revealed that downregulation of CCMAlnc impaired CRC cell proliferation and invasion in vitro, but upregulation of CCMAlnc reversed this effect. Moreover, CCMAlnc was validated to act as a competing endogenous RNA (ceRNA) that stabilizes the expression of HES6 by downregulating miR-5001-5p. Conclusions: CCMAlnc/miR-5001-5p/HES6 signaling is strongly activated to promote CRC malignance. CCMAlnc is defined as a potential candidate biomarker for metastasis prediction in CRC patients and as a potential therapeutic target for CRC treatment.